Method for treating open-pit coal mine brackish water by using coal gangue

CN122958006APending Publication Date: 2026-10-23XINJIANG HAMI SANTANGHU ENERGY DEV & CONSTR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611283263.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种利用煤矸石协同处理露天煤矿苦咸水的方法,解决了现有露天煤矿苦咸水处理工艺中化学药剂消耗量偏大、污染物质去除成本偏高,固废煤矸石未能得到资源化利用,同时沉淀料浆固液分离阻力偏大导致脱水滤饼含水率偏高,并且水体内残余的细小悬浮物容易引发后续反渗透膜污堵的问题

Benefits of technology

1、本发明将热活化煤矸石粉体引入露天煤矿苦咸水处理流程中,配合投加氢氧化钙干粉和液体硅酸钠,促使煤矸石内部的硅氧键和铝氧键发生断裂并溶出活性离子;溶出的活性物质同苦咸水内部的硫酸根离子和溶解态钙离子结合生成硫铝酸钙水化物沉淀,同步去除了水体内的可溶性污染物质,实现了固体废弃物资源化消耗和矿区苦咸水净化的协同处理。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958006A_ABST
    Figure CN122958006A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of water treatment, and discloses a method for treating open-pit coal mine bitter-salty water by using coal gangue, which comprises the following steps: adding hot activated coal gangue powder into the open-pit coal mine bitter-salty water, adding liquid sodium silicate and sodium gluconate to prepare primary slurry; adding calcium hydroxide dry powder into the primary slurry, heating and performing constant temperature dissolution reaction to obtain excited slurry; controlling the heating rate and performing constant temperature aging under a low shear flow field to generate composite precipitation slurry; performing pressure filtration and dehydration on the composite precipitation slurry to collect dewatered filter cake and high-temperature filtrate; after cooling, introducing carbon dioxide gas to adjust the pH value, adding polyacrylamide aqueous solution, and introducing into an ultrafiltration membrane assembly to filter to obtain reverse osmosis pretreatment effluent water. Through the regulation and control of coal gangue and reagents, the present application promotes the generation of precipitates by combining active ions with pollutants, improves the dehydration performance through temperature control and aging, and finally deeply purifies the water body and reduces the risk of subsequent membrane blockage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment technology, specifically a method for co-treating brackish water from open-pit coal mines using coal gangue. Background Technology

[0002] Open-pit coal mines generate significant amounts of brackish water during operations. This water contains high concentrations of sulfate and free calcium and magnesium ions. Conventional brackish water purification processes often rely on adding large doses of commercially available chemical agents to precipitate and remove soluble pollutants, resulting in high overall operating costs. Coal gangue, a solid waste generated during coal mining, can easily occupy land resources and pose environmental pollution risks if left untreated for extended periods. Current treatment models treat brackish water purification and coal gangue disposal independently, failing to establish a coordinated treatment approach. Consequently, solid waste is not effectively converted into resources for water treatment.

[0003] When treating brackish water in mining areas using conventional chemical precipitation methods, the resulting precipitates are small and loosely structured. Existing processes neglect the aging and agglomeration of the precursors, resulting in a large number of fine flocs remaining in the slurry. When the uncontrolled slurry is directly pumped into conventional filter presses for solid-liquid separation, problems arise such as high liquid phase viscosity and high filtration resistance, leading to a high moisture content in the resulting dewatered filter cake. This increases the physical volume and transportation burden of the filter cake for disposal.

[0004] The water produced after front-end sedimentation and separation often retains high alkalinity and fine suspended solids. Conventional operations often use direct addition of inorganic acid to adjust the water's pH, which carries the risk of introducing impurity ions into the treatment system. If the remaining fine suspended solids in the water are not retained, they can easily cause physical fouling and chemical scaling when they enter the subsequent reverse osmosis membrane modules, increasing the frequency of cleaning the core membrane elements and the operational resistance of the entire water treatment system. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for co-treating brackish water from open-pit coal mines using coal gangue. This method solves the problems of excessive chemical reagent consumption, high cost of pollutant removal, failure to utilize solid waste coal gangue as a resource in existing open-pit coal mine brackish water treatment processes, high resistance in solid-liquid separation of sediment slurry leading to high moisture content in dewatered filter cake, and the tendency of residual fine suspended solids in the water to cause fouling of subsequent reverse osmosis membranes.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for co-treating brackish water from open-pit coal mines using coal gangue, employing the following technical solution: A method for co-treating brackish water from open-pit coal mines using coal gangue includes the following steps: Under stirring conditions, thermally activated coal gangue powder is added to the brackish water of the open-pit coal mine. After mixing evenly, liquid sodium silicate is added in a pulse manner, followed by sodium gluconate and continuous mixing to form a slurry, thus obtaining a primary slurry. Calcium hydroxide powder was added to the primary slurry to increase the pH value of the system, followed by heating and constant-temperature dissolution reaction to obtain an activated slurry. The heating rate is controlled to heat the activating slurry, the stirring speed is reduced, and the slurry is aged at a constant temperature under a low shear flow field to generate a composite precipitate slurry. The composite precipitate slurry is pumped to a filter press for dewatering, and the dewatered filter cake and high-temperature filtrate are collected after unloading. The high-temperature filtrate is cooled to obtain a cooled filtrate. Carbon dioxide gas is introduced to adjust the pH value of the cooled filtrate. An aqueous solution of polyacrylamide is added as a micro-flocculator. The solution is then introduced into an ultrafiltration membrane module for filtration and separation, where fine colloids are retained. The pretreated reverse osmosis effluent is collected.

[0007] By adopting the above technical solution, and through the use of thermally activated coal gangue combined with specific reagents for reaction regulation, a synergistic effect of removing pollutants from water while simultaneously achieving solid waste resource utilization is achieved. The reaction process and principle steps of this invention mainly include: The added liquid sodium silicate reacts with magnesium ions in the brackish water of the open-pit coal mine to form an amorphous magnesium silicate precipitate precursor. The corresponding reaction formula is: Mg 2+ +SiO3 2- +H2O→MgSiO3·H2O↓; The sodium gluconate added thereafter has hydroxyl and carboxyl functional groups. After attaching to the surface of the thermally activated coal gangue powder, it can generate a steric hindrance effect, which helps to slow down the dense coating phenomenon of the amorphous magnesium silicate precipitate precursor on the surface of solid particles, thereby maintaining the relative unobstructed release channels of internal active substances.

[0008] Adding calcium hydroxide powder increases the alkalinity of the liquid phase. Under alkaline conditions combined with heating, the silicon-oxygen bonds and aluminum-oxygen bonds in the thermally activated coal gangue powder break, thereby releasing active aluminate ions and silicate ions. The released active aluminate ions combine with sulfate ions and dissolved calcium ions in the brackish water of the open-pit coal mine, undergoing a hydration reaction to form calcium sulfoaluminate hydrate precipitate of ettringite. The reaction formula is as follows: 6Ca 2+ +2AlO2 - +3SO4 2- +4OH -+26H2O→3CaO·Al2O3·3CaSO4·32H2O↓.

[0009] After entering the aging conditions, relying on the low shear flow field and slow heating state, the calcium sulfoaluminate hydrate and the amorphous magnesium silicate precipitate precursor tend to co-aggregate; with the formation of large-volume composite precipitates, they can capture suspended impurities remaining in the water during the sedimentation process.

[0010] After cooling, carbon dioxide gas is introduced, which reacts with the residual hydroxide ions in the system to generate carbonate ions, which then combine with excess calcium ions to form calcium carbonate precipitate, thus adjusting the pH value of the water. Subsequently, the adsorption bridging effect of the polyacrylamide aqueous solution is used to aggregate micron-sized suspended matter into fine colloids, which are then physically retained by the ultrafiltration membrane module.

[0011] Preferably, the method for preparing the thermally activated coal gangue powder includes the following steps: The raw coal gangue is crushed and mixed evenly to obtain crushed and homogenized material; The crushed and homogenized material is fed into a heating furnace and heated at a heating rate of 5°C / min. It is then kept at a constant temperature of 700°C to 800°C for 1.0 to 2.0 hours to undergo a dehydroxylation phase transition reaction, resulting in calcined clinker. The calcined clinker is cooled to 25°C, pulverized and sieved, and powder with a particle size not greater than 74 μm is collected to obtain the thermally activated coal gangue powder.

[0012] By adopting the above technical solution, the kaolinite mineral contained in the original coal gangue loses its structural hydroxyl groups under high-temperature calcination, and its crystal structure is destroyed, transforming into a thermodynamically unstable metakaolinite phase; under the combined conditions of specific temperature range and holding time, the aluminum-oxygen octahedral coordination is transformed into tetrahedral or pentahedral coordination, which improves the material's reactivity and dissolution rate in alkaline environments; at the same time, limiting the powder particle size increases the solid-liquid contact area of ​​the reaction system.

[0013] Preferably, the solid-liquid mass ratio of the thermally activated coal gangue powder to the brackish water from the open-pit coal mine is 1:6 to 1:4; the molar ratio of silica in the liquid sodium silicate to magnesium ions in the brackish water from the open-pit coal mine is 1.5:1 to 2.5:1; after adding the liquid sodium silicate, the pH value of the system is between 8.5 and 9.5; the amount of sodium gluconate added is 0.1% to 0.3% of the total mass of the thermally activated coal gangue powder; the stirring speed of the continuous mixing and slurry preparation is set to 120 rpm to 150 rpm, and the continuous mixing and slurry preparation time is 30 minutes to 45 minutes.

[0014] By adopting the above technical solutions, the setting of the solid-liquid mass ratio is conducive to maintaining the supply of aluminum source in the reaction system; the molar ratio parameter of silica to magnesium ions promotes the transformation of free magnesium ions in water into silicate form; the specific pH environment helps sodium silicate to undergo moderate dissociation; the trace addition of sodium gluconate can reduce the introduction of excess organic carbon source while maintaining the surface coordination effect; the continuous mixing and pulping at a higher speed provides shear mixing force, promoting the materials of different densities to achieve a better uniform dispersion state at both the macroscopic and microscopic scales.

[0015] Preferably, during the process of adding calcium hydroxide dry powder to the primary slurry, the molar ratio of the total effective calcium provided by the dissolved calcium ions in the brackish water of the open-pit coal mine and the added calcium hydroxide dry powder to the sulfate ions in the brackish water of the open-pit coal mine is controlled to be 3.0:1 to 3.5:1, and the pH value of the system is raised to 11.5 to 12.0; the heating temperature of the isothermal dissolution reaction is set to 40°C to 45°C, and the time of the isothermal dissolution reaction is 1.5 hours to 2.0 hours.

[0016] By adopting the above technical solution, the set total calcium to sulfate ratio is mainly to meet the stoichiometric conditions required for the formation of calcium sulfoaluminate hydrate; the target pH value enables the solution to have a certain alkaline depolymerization ability, which is conducive to the breaking and disintegration of inorganic polymer networks; the specified heating temperature provides thermodynamic conditions to cross the reaction activation energy barrier and accelerate the ion migration rate; combined with the set isothermal dissolution reaction time, the material obtains a reasonable contact period, which helps to improve the leaching performance of effective components.

[0017] Preferably, during the process of controlling the heating rate to heat the stimulating slurry, the heating rate is 1.5℃ / min to 2.5℃ / min, and the target heating temperature is 55℃ to 65℃; the stirring speed for the constant temperature aging is set to 40rpm to 60rpm, and the constant temperature aging time is 2.5 hours to 3.0 hours.

[0018] By adopting the above technical solutions, the controlled slow heating state reduces the risk of local overheating in the system, alleviates the nucleation reaction caused by excessive supersaturation, and is conducive to the regular growth of new phases along existing crystal nuclei. Maintaining a low shear flow field during the aging stage reduces the probability of the formed hydrate flocs being destroyed by mechanical external forces, maintains the growth trend of composite precipitate particle size, and thus improves the physical sedimentation and dewatering performance of the final slurry.

[0019] Preferably, the filter press is a diaphragm plate and frame filter press; the filter press dewatering directly dewaters the composite precipitate slurry at a temperature of 55°C to 65°C, with the feed pressure controlled at 0.4MPa to 0.6MPa and the pressing pressure controlled at 1.0MPa to 1.2MPa.

[0020] By adopting the above technical solution, the pressure filtration and dewatering operation is carried out directly at a relatively high temperature. Taking advantage of the relatively low viscosity of the liquid phase at high temperature, it helps to reduce the resistance of the filtrate through the filter cake layer. Combined with the high-pressure secondary pressing function of the diaphragm plate and frame filter press, the capillary water remaining in the gaps between the filter cake particles is forced out, resulting in dewatered solids with low moisture content, which to a certain extent reduces the volume and related costs of subsequent solid waste disposal.

[0021] Preferably, the high-temperature filtrate is cooled to obtain a cooled filtrate with a temperature of 40°C to 45°C; the volume purity of the carbon dioxide gas is 99.5%; the pH value of the cooled filtrate after cooling is 7.0 to 8.5; the mass fraction of the polyacrylamide aqueous solution is 0.1%, and the effective dosage is 3.0 mg / L.

[0022] By adopting the above technical solutions, lowering the fluid temperature helps increase the solubility of carbon dioxide gas in the aqueous phase; the introduction of high-purity gas reduces the risk of introducing impurity gases into the treatment system; the pH adjustment operation consumes excess alkalinity, making the effluent quality closer to the feed water requirements of subsequent membrane treatment processes; specific concentrations and dosages of polyacrylamide can trigger the adsorption and bridging effect of long polymer chains, thereby capturing residual fine colloidal particles and slowing down the fouling process of the reverse osmosis membrane.

[0023] Preferably, the continuous mixing and pulping, the constant temperature dissolution reaction, and the constant temperature aging are all carried out in an intermittent stirred reactor equipped with a variable frequency stirring device and a steam heating jacket.

[0024] By adopting the above technical solutions, multiple operation steps can be completed in the same equipment, simplifying the material conveying steps and the layout of related process pipelines; the variable frequency stirring device has the function of switching from higher speed to lower speed to match the different requirements of shear flow field for different reaction stages; the surface heat transfer mode provided by the steam heating jacket is relatively uniform, reducing the probability of local coking and scaling caused by point heating.

[0025] Preferably, the filter press dewatering operation is as follows: the composite sediment slurry is pumped into the diaphragm plate and frame filter press, and after the feeding is completed, the diaphragm press is started for dewatering.

[0026] By adopting the above technical solution, the filling degree of the filter chamber is judged based on the change of feed flow rate, which is beneficial to collect more solids in the filter chamber before performing the pressing action; low-pressure feeding filtration is performed first, and the pressure control setting of diaphragm pressing is combined with the pressure rise in the initial stage to alleviate the clogging of filter cloth pores caused by the pressure rise, which helps to extend the service life of the filter media, while maintaining the dewatering performance of each operation cycle.

[0027] Preferably, a microporous aeration disc is used to introduce carbon dioxide gas into the cooled filtrate.

[0028] By adopting the above technical solution, the microporous aeration disc disperses the continuous airflow into a relatively dense group of microbubbles. Since the microbubbles rise slowly in the water and have a large specific surface area, the contact area and mass transfer time of the gas and liquid phases are increased. This helps to improve the absorption and utilization rate of carbon dioxide gas and shortens the time of pH value adjustment to a certain extent.

[0029] This invention provides a method for co-treating brackish water from open-pit coal mines using coal gangue, which has the following beneficial effects: 1. This invention introduces thermally activated coal gangue powder into the brackish water treatment process of open-pit coal mines, and adds dry calcium hydroxide powder and liquid sodium silicate to promote the breakage of silicon-oxygen bonds and aluminum-oxygen bonds inside the coal gangue and dissolve active ions. The dissolved active substances combine with sulfate ions and dissolved calcium ions in the brackish water to form calcium sulfoaluminate hydrate precipitate, which simultaneously removes soluble pollutants in the water, realizing the synergistic treatment of solid waste resource consumption and brackish water purification in the mining area.

[0030] 2. This invention heats the slurry by controlling the heating rate and aging it at a constant temperature under a low shear flow field, which promotes the co-aggregation of different types of precipitation precursors and forms large composite precipitate particles. Subsequently, it directly performs pressure filtration and dewatering at a relatively high temperature. It utilizes the physical property that the liquid phase has a lower kinematic viscosity at high temperature to reduce filtration resistance. Combined with diaphragm pressing, it obtains a dewatered filter cake with a low moisture content, which improves the solid-liquid separation performance of the slurry and reduces the volume of filter cake to be disposed of.

[0031] 3. In this invention, carbon dioxide gas is introduced into the cooled high-temperature filtrate. The carbon dioxide reacts with the residual hydroxide ions in the water to generate carbonate ions, which then combine with excess calcium ions to form calcium carbonate precipitate, thus completing the pH adjustment operation of the water. In conjunction with the addition of polyacrylamide aqueous solution to induce the long-chain adsorption and bridging effect of polymers, the residual fine suspended matter is aggregated into microcolloids and physically intercepted by the ultrafiltration membrane module, reducing the risk of fouling of the subsequent reverse osmosis membrane. Attached Figure Description

[0032] Figure 1 The X-ray diffraction patterns of the coal gangue powders obtained in each preparation example of the present invention are shown below. Figure 2 The X-ray diffraction pattern of the dehydrated filter cake in Example 2 of the present invention; Figure 3 The scatter plot and fitting graph of the t / V and V relationship for the resistivity test of slurry filter cake in the embodiments and comparative examples of the present invention; Figure 4The following are anion chromatograms of the final effluent from each group of the present invention; Figure 5 This is a graph showing the change in filtration time for each group of water samples in the silt density index test according to the present invention. Detailed Implementation

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] The brackish water from the open-pit coal mine was taken from the actual mining area. To ensure the parallel comparability of the test data from each embodiment and comparative example, a reference water sample was used, which had undergone membrane pretreatment to remove large suspended particles. This reference water sample was calibrated by ion chromatography and inductively coupled plasma atomic emission spectrometry, with an initial pH of 7.2 and the concentration of the main pollutant ion fixed at SO42-. 2- Concentration 8652.5 mg / L, Ca 2+ Concentration 1273.5 mg / L, Mg 2+ Concentration 2146.8 mg / L.

[0035] The undisturbed coal gangue was obtained from the waste rock stripped during coal mining. X-ray fluorescence spectroscopy analysis revealed its main chemical composition to be: SiO2 52.3%, Al2O3 31.5%, Fe2O3 3.2%, CaO 1.5%, MgO 0.8%, and loss on ignition 10.7%. X-ray diffraction analysis confirmed that its main crystalline mineral phases were kaolinite and quartz, serving as the baseline raw material for preparing thermally activated coal gangue precursors.

[0036] The common name for liquid sodium silicate is water glass, with CAS number 1344-09-8 and chemical formula Na2O·nSiO2. In this example, an industrial-grade product with a modulus n of 2.4 was selected, and its SiO2 mass fraction was 27.3% and Na2O mass fraction was 11.7%.

[0037] Sodium gluconate has the CAS number 527-07-1 and the molecular formula C6H. 11 NaO7 is made from industrial-grade powder with an effective purity greater than 98.5%.

[0038] The CAS number for calcium hydroxide is 1305-62-0, and the molecular formula is Ca(OH)2. Industrial-grade dry powder with an effective mass fraction greater than 90.0% and a sieve residue of less than 1.0% on a 200-mesh standard test sieve is selected.

[0039] The carbon dioxide gas has the CAS number 124-38-9 and the molecular formula CO2. A liquefied bottled gas with a volume purity of 99.5% was selected.

[0040] The micro-flocculator polyacrylamide has the CAS number 9003-05-8 and the repeating unit molecular formula is (C3H5NO)n. It is an industrial-grade anionic powder with a number-average molecular weight of 12 million and a degree of hydrolysis of 20%.

[0041] Preparation Example 1: This preparation example provides a method for preparing thermally activated coal gangue, including the following steps: (1) Weigh 1000g of standard raw coal gangue, crush it to a particle size of less than or equal to 10mm using a jaw crusher, and mix it evenly to obtain crushed homogenized material; (2) The crushed and homogenized material obtained in step (1) is fed into a box-type resistance furnace and heated to 700°C at a heating rate of 5°C / min. It is then kept at 700°C for 1.0 hour to undergo a dehydroxylation phase change reaction and obtain calcined clinker. (3) The calcined clinker obtained in step (2) is taken out of the furnace and quickly cooled to room temperature of 25°C. Then it is fed into Raymond mill for crushing, passed through a 200-mesh standard test sieve, and the sieve material with a particle size less than or equal to 74μm is collected to obtain thermally activated coal gangue powder.

[0042] Preparation Example 2: This preparation example provides a method for preparing thermally activated coal gangue, including the following steps: (1) Weigh 1000g of standard raw coal gangue, crush it to a particle size of less than or equal to 10mm using a jaw crusher, and mix it evenly to obtain crushed homogenized material; (2) The crushed and homogenized material obtained in step (1) is fed into a box-type resistance furnace and heated to 750°C at a heating rate of 5°C / min. It is then kept at 750°C for 1.5 hours to undergo a dehydroxylation phase transition reaction and obtain calcined clinker. (3) The calcined clinker obtained in step (2) is taken out of the furnace and quickly cooled to room temperature of 25°C. Then it is fed into Raymond mill for crushing, passed through a 200-mesh standard test sieve, and the sieve material with a particle size less than or equal to 74μm is collected to obtain thermally activated coal gangue powder.

[0043] Preparation Example 3: This preparation example provides a method for preparing thermally activated coal gangue, including the following steps: (1) Weigh 1000g of standard raw coal gangue, crush it to a particle size of less than or equal to 10mm using a jaw crusher, and mix it evenly to obtain crushed homogenized material; (2) The crushed and homogenized material obtained in step (1) is fed into a box-type resistance furnace and heated to 800°C at a heating rate of 5°C / min. It is then kept at 800°C for 2.0 hours to undergo a dehydroxylation phase change reaction and obtain calcined clinker. (3) The calcined clinker obtained in step (2) is taken out of the furnace and quickly cooled to room temperature of 25°C. Then it is fed into Raymond mill for crushing, passed through a 200-mesh standard test sieve, and the sieve material with a particle size less than or equal to 74μm is collected to obtain thermally activated coal gangue powder.

[0044] Preparation Example 4: This preparation example provides a method for preparing unactivated reference coal gangue, including the following steps: (1) Weigh 1000g of standard raw coal gangue, crush it to a particle size of less than or equal to 10mm using a jaw crusher, and mix it evenly to obtain crushed homogenized material; (2) The crushed and homogenized material obtained in step (1) is directly fed into Raymond mill at room temperature of 25°C and crushed without heating and calcination. The material is passed through a 200-mesh standard test sieve and the sieve material with a particle size of less than or equal to 74μm is collected to obtain unactivated reference coal gangue powder.

[0045] Example 1: This embodiment provides a method for co-treating brackish water from open-pit coal mines using coal gangue, comprising the following steps: (1) At room temperature of 25°C, 10L of the above-mentioned standard open-pit coal mine brackish water was injected into an intermittent stirred reactor equipped with a variable frequency stirring device and a steam heating jacket. 1.67kg of thermally activated coal gangue powder obtained in Preparation Example 1 was added according to a solid-liquid mass ratio of 1:6, and stirring was started. Subsequently, liquid sodium silicate was added in a pulsed manner according to a molar ratio of 1.5:1 between the added silica and magnesium ions in the raw water. At this time, the pH value of the system was between 8.5 and 9.5. Then, 1.67g of sodium gluconate (i.e., the amount added was 0.1% of the total mass of thermally activated coal gangue) was added, and the stirring speed was set to 120rpm. The mixture was continuously mixed and slurried for 30 minutes to obtain the primary slurry. (2) Maintain the stirring speed of 120 rpm in the reactor of step (1), slowly add calcium hydroxide dry powder to the primary slurry, use an online pH meter to monitor dynamically, and combine the control requirement that the total effective calcium provided by dissolved calcium ions in the raw water and added calcium hydroxide is 3.0:1 with the molar ratio of sulfate ions in the raw water to complete the addition, raise the pH value of the slurry system to 11.5; then turn on the steam heating jacket to raise the system temperature to 40℃, and keep the dissolution reaction at 40℃ for 1.5 hours to obtain the activated slurry; (3) After the constant temperature dissolution stage in step (2), the temperature of the slurry in the reactor is further increased to 55℃ at a heating rate of 1.5℃ / min. When the temperature reaches 55℃, the speed of the variable frequency stirrer is reduced to 40rpm in a low shear flow field state, and the mixture is aged at 55℃ for 2.5 hours to generate a composite precipitate slurry. (4) After the aging process in step (3), without cooling, the composite precipitate slurry at 55°C is directly pumped into the diaphragm plate and frame filter press. The feed is fed at a feed pressure of 0.4 MPa. After the feed is completed, the diaphragm press is turned on and the filter is dehydrated at a pressing pressure of 1.0 MPa. After unloading, the dehydrated filter cake and the high-temperature filtrate are collected separately. (5) Pump the high-temperature filtrate separated in step (4) into a heat exchanger and cool it down to 40°C to obtain a cooled filtrate. Introduce carbon dioxide gas with a volume purity of 99.5% into the cooled filtrate using a microporous aeration disc to adjust the pH value of the water to 7.0. Then add a prepared polyacrylamide aqueous solution with a mass fraction of 0.1% as a micro-flocculator, control the effective dosage of polyacrylamide to 3.0 mg / L, introduce it into the ultrafiltration membrane module for filtration and separation, retain the fine colloids, and collect the reverse osmosis pretreated effluent that meets the physical water quality requirements.

[0046] Example 2: This embodiment provides a method for co-treating brackish water from open-pit coal mines using coal gangue, comprising the following steps: (1) At room temperature of 25°C, 10L of the above-mentioned standard open-pit coal mine brackish water was injected into an intermittent stirred reactor equipped with a variable frequency stirring device and a steam heating jacket. 2.0kg of the thermally activated coal gangue powder obtained in Preparation Example 2 was added according to a solid-liquid mass ratio of 1:5, and stirring was started. Subsequently, liquid sodium silicate was added in a pulsed manner according to a molar ratio of 2.0:1 between the added silica and the magnesium ions in the raw water. At this time, the pH value of the system was between 8.5 and 9.5. Then, 4.0g of sodium gluconate (i.e., the amount added was 0.2% of the total mass of the thermally activated coal gangue) was added, and the stirring speed was set to 135rpm. The mixture was continuously mixed and slurried for 40 minutes to obtain the primary slurry. (2) Maintain the stirring speed of 135 rpm in the reactor of step (1), slowly add calcium hydroxide dry powder to the primary slurry, use an online pH meter to monitor dynamically, and combine the control requirement that the total effective calcium provided by dissolved calcium ions in the raw water and added calcium hydroxide is 3.2:1 with the molar ratio of sulfate ions in the raw water to complete the addition, raise the pH value of the slurry system to 11.8; then turn on the steam heating jacket to raise the system temperature to 42℃, and keep the dissolution reaction at 42℃ for 1.8 hours to obtain the activated slurry; (3) After the constant temperature dissolution stage in step (2), the temperature of the slurry in the reactor is further increased to 60℃ at a heating rate of 2.0℃ / min; when the temperature reaches 60℃, the speed of the variable frequency stirrer is reduced to 50rpm in a low shear flow field state, and the mixture is aged at 60℃ for 2.8 hours to generate a composite precipitate slurry. (4) After the aging process in step (3), without cooling, the composite precipitate slurry at 60°C is directly pumped into the diaphragm plate and frame filter press. The feed is fed at a feed pressure of 0.5MPa. After the feed is completed, the diaphragm press is turned on and the filter is dehydrated at a pressing pressure of 1.1MPa. After unloading, the dehydrated filter cake and the high-temperature filtrate are collected separately. (5) The high-temperature filtrate separated in step (4) is pumped into a heat exchanger and cooled to 42°C to obtain a cooled filtrate. Carbon dioxide gas with a volume purity of 99.5% is introduced into the cooled filtrate using a microporous aeration disc to adjust the pH value of the water to 7.5. Then, a prepared polyacrylamide aqueous solution with a mass fraction of 0.1% is added as a micro-flocculator. The effective dosage of polyacrylamide is controlled to be 3.0 mg / L. The solution is introduced into an ultrafiltration membrane module for filtration and separation, and fine colloids are retained. The reverse osmosis pretreated effluent that meets the physical water quality requirements is collected.

[0047] Example 3: This embodiment provides a method for co-treating brackish water from open-pit coal mines using coal gangue, comprising the following steps: (1) At room temperature of 25°C, 10L of the above-mentioned standard open-pit coal mine brackish water was injected into an intermittent stirred reactor equipped with a variable frequency stirring device and a steam heating jacket. 2.5kg of the thermally activated coal gangue powder obtained in Preparation Example 3 was added according to a solid-liquid mass ratio of 1:4, and stirring was started. Subsequently, liquid sodium silicate was added in a pulsed manner according to a molar ratio of 2.5:1 between the added silica and the magnesium ions in the raw water. At this time, the pH value of the system was between 8.5 and 9.5. Then, 7.5g of sodium gluconate (i.e., the amount added was 0.3% of the total mass of the thermally activated coal gangue) was added, and the stirring speed was set to 150rpm. The mixture was continuously mixed and slurried for 45 minutes to obtain the primary slurry. (2) Maintain the stirring speed of 150 rpm in the reactor of step (1), slowly add calcium hydroxide dry powder to the primary slurry, use an online pH meter to monitor dynamically, and combine the control requirement that the total effective calcium provided by dissolved calcium ions in the raw water and added calcium hydroxide is 3.5:1 with the molar ratio of sulfate ions in the raw water to complete the addition, raise the pH value of the slurry system to 12.0; then turn on the steam heating jacket to raise the system temperature to 45℃, and keep the dissolution reaction at 45℃ for 2.0 hours to obtain the activated slurry; (3) After the constant temperature dissolution stage in step (2), the temperature of the slurry in the reactor is further increased to 65℃ at a heating rate of 2.5℃ / min; when the temperature reaches 65℃, the speed of the variable frequency stirrer is reduced to 60rpm in a low shear flow field state, and the mixture is aged at 65℃ for 3.0 hours to generate a composite precipitate slurry. (4) After the aging process in step (3), without cooling, the composite precipitate slurry at 65°C is directly pumped into the diaphragm plate and frame filter press. The feed is fed at a feed pressure of 0.6MPa. After the feed is completed, the diaphragm press is turned on and the filter is dehydrated at a pressing pressure of 1.2MPa. After unloading, the dehydrated filter cake and the high-temperature filtrate are collected separately. (5) The high-temperature filtrate separated in step (4) is pumped into a heat exchanger and cooled to 45°C to obtain a cooled filtrate. Carbon dioxide gas with a volume purity of 99.5% is introduced into the cooled filtrate using a microporous aeration disc to adjust the pH value of the water to 8.5. Then, a prepared polyacrylamide aqueous solution with a mass fraction of 0.1% is added as a micro-flocculator. The effective dosage of polyacrylamide is controlled to be 3.0 mg / L. The solution is introduced into an ultrafiltration membrane module for filtration and separation, and fine colloids are retained. The reverse osmosis pretreated effluent that meets the physical water quality requirements is collected.

[0048] Example 4: This embodiment provides a method for co-treating brackish water from open-pit coal mines using coal gangue, comprising the following steps: (1) At room temperature of 25°C, 10L of the above-mentioned standard open-pit coal mine brackish water was injected into an intermittent stirred reactor equipped with a variable frequency stirring device and a steam heating jacket. 2.0kg of the thermally activated coal gangue powder obtained in Preparation Example 2 was added according to a solid-liquid mass ratio of 1:5, and stirring was started. Subsequently, liquid sodium silicate was added in a pulsed manner according to a molar ratio of 2.0:1 between the added silica and the magnesium ions in the raw water. At this time, the pH value of the system was between 8.5 and 9.5. Then, 4.0g of sodium gluconate (i.e., the amount added was 0.2% of the total mass of the thermally activated coal gangue) was added, and the stirring speed was set to 135rpm. The mixture was continuously mixed and slurried for 40 minutes to obtain the primary slurry. (2) Maintain the stirring speed of 135 rpm in the reactor of step (1), slowly add calcium hydroxide dry powder to the primary slurry, and complete the addition in accordance with the control requirement that the total effective calcium provided by the dissolved calcium ions in the raw water and the added calcium hydroxide is 3.5:1 with the molar ratio of sulfate ions in the raw water, thereby raising the pH value of the slurry system to 12.0; then turn on the steam heating jacket to raise the system temperature to 42°C, and keep the dissolution reaction at 42°C for 1.8 hours to obtain the activated slurry; (3) After the constant temperature dissolution stage in step (2), the temperature of the slurry in the reactor is further increased to 60℃ at a heating rate of 2.0℃ / min; when the temperature reaches 60℃, the speed of the variable frequency stirrer is reduced to 50rpm in a low shear flow field state, and the mixture is aged at 60℃ for 2.8 hours to generate a composite precipitate slurry. (4) After the aging process in step (3), without cooling, the composite precipitate slurry at 60°C is directly pumped into the diaphragm plate and frame filter press. The feed is fed at a feed pressure of 0.5MPa. After the feed is completed, the diaphragm press is turned on and the filter is dehydrated at a pressing pressure of 1.1MPa. After unloading, the dehydrated filter cake and the high-temperature filtrate are collected separately. (5) The high-temperature filtrate separated in step (4) is pumped into a heat exchanger and cooled to 42°C to obtain a cooled filtrate. Carbon dioxide gas with a volume purity of 99.5% is introduced into the cooled filtrate using a microporous aeration disc to adjust the pH value of the water to 7.5. Then, a prepared polyacrylamide aqueous solution with a mass fraction of 0.1% is added as a micro-flocculator. The effective dosage of polyacrylamide is controlled to be 3.0 mg / L. The solution is introduced into an ultrafiltration membrane module for filtration and separation, and fine colloids are retained. The reverse osmosis pretreated effluent that meets the physical water quality requirements is collected.

[0049] Comparative Example 1: Compared with Example 2, the difference is that in step (1), the unactivated reference coal gangue powder obtained in Preparation Example 4 is added instead of the thermally activated coal gangue powder obtained in Preparation Example 2. All other aspects are the same.

[0050] Comparative Example 2: Compared with Example 2, the difference is that the process sequence of magnesium ion selective precipitation is disrupted. Liquid sodium silicate is not added in step (1). Instead, the calculated amount of liquid sodium silicate is added to the slurry system in step (2) simultaneously with the dry calcium hydroxide powder (i.e., added when the slurry system is in a strongly alkaline state). The rest are the same.

[0051] Comparative Example 3: Compared with Example 2, the difference is that the crystallization surface coordination and slowing regulation are missing, and sodium gluconate is not added in step (1), but the rest are the same.

[0052] Comparative Example 4: Compared with Example 2, the difference is that the medium-temperature stable crystallization temperature zone is removed. In step (3), the temperature of the stimulating slurry in the reactor is raised to 85°C at the same heating rate and aged at a constant temperature of 85°C for 2.8 hours. The rest are the same.

[0053] Comparative Example 5: Compared with Example 2, the difference is that the acidifier in the reverse osmosis membrane pretreatment stage is different. In step (5), industrial sulfuric acid with a mass fraction of 30.0% is used to replace carbon dioxide gas to adjust the pH value of the water. All other aspects are the same.

[0054] Test Example 1: This test example aims to verify the effect of thermodynamic calcination on the crystal phase structure of coal gangue and to evaluate its ability to release available aluminum. The thermally activated coal gangue powders obtained in Preparation Examples 1 to 3, and the unactivated reference coal gangue powder obtained in Preparation Example 4 were used as test objects for relevant tests. The experimental steps are as follows: (1) Weigh 2.0g of each of the powder samples obtained in Preparation Examples 1 to 4 and grind them further in an agate mortar until there is no obvious particle feel. Then, use an X-ray diffractometer to perform phase structure scanning analysis on each sample. The test conditions are set as Cu-Kα radiation source, tube voltage 40kV, tube current 40mA, scanning angle range 2θ set to 5 degrees to 60 degrees, scanning step size set to 0.02 degrees, and record the diffraction pattern data of each sample.

[0055] (2) Weigh 2.0 g of each of the powder samples obtained in Preparation Examples 1 to 4 and place them in polytetrafluoroethylene reaction flasks. Add 100 mL of sodium hydroxide aqueous solution with an initial pH of 12.0 to each reaction flask, and maintain the pH of the system at 12.0 ± 0.1 by titration during the constant temperature leaching reaction. Place the reaction flasks in a constant temperature water bath shaker, set the water bath temperature to 45 °C, the shaking speed to 150 rpm, and carry out the constant temperature leaching reaction for 2.0 hours.

[0056] (3) After the leaching reaction is completed, transfer the mixture in each reaction flask to a centrifuge tube and centrifuge at 8000 rpm for 10 minutes. Take the supernatant and acidify it with 5% nitric acid solution to make up the volume.

[0057] (4) The mass concentration of aluminum ions in the solution after volume adjustment was determined by inductively coupled plasma atomic emission spectrometry, and the effective aluminum dissolution rate was calculated by combining the initial mass of the sample and the total mass fraction of aluminum oxide in the original sample.

[0058] The relevant data on the effective aluminum leaching performance obtained after the above tests are shown in Table 1.

[0059] Table 1. Test data on the effective aluminum leaching performance of coal gangue powder obtained from each preparation example in conclusion: Based on the data in Table 1 and the appendix Figure 1 This allows for the analysis of phase transitions and effective aluminum dissolution characteristics of coal gangue precursors before and after thermal activation. Figure 1 The diffraction pattern in (a) shows that Preparation Example 4 exhibits characteristic kaolinite diffraction peaks in the low diffraction angle region, indicating that the undisturbed coal gangue has a relatively complete crystal structure. Combined with the dissolution test results in Table 1, the effective aluminum dissolution rate of Preparation Example 4 under alkaline conditions is 1.92%. This indicates that in unactivated undisturbed coal gangue, aluminum exists within a stable aluminosilicate lattice and is difficult to dissolve in large quantities.

[0060] Depend on Figure 1 (b) It can be seen that after calcination, the original characteristic diffraction peaks of kaolinite in Preparation Example 2 basically disappeared, and amorphous broad peaks appeared in the 20° to 30° range. This indicates that the coal gangue underwent a dehydroxylation reaction during calcination, and the kaolinite crystalline phase transformed into the metakaolinite phase. Combined with the data in Table 1, the effective aluminum dissolution rates of Preparation Examples 1 to 3 were significantly improved compared to Preparation Example 4, with the effective aluminum dissolution rates of Preparation Examples 2 and 3 reaching 73.65% and 77.14%, respectively.

[0061] The test data above indicate that heat treatment can alter the original stable crystal structure of coal gangue, transforming it into an amorphous phase. In this state, the coordination of aluminum changes, allowing it to dissolve into the liquid phase as aluminate ions in alkaline solutions. These results confirm that the thermal activation process can enhance the reactivity of the aluminum component in coal gangue, providing the necessary material basis for subsequent ion precipitation and mineralization reactions in the system.

[0062] Test Example 2: This test example is used to test the phase composition of the solid product generated by the reaction system. The dehydrated filter cake obtained in Example 2 is used as the test object, and relevant tests are carried out. The experimental steps are as follows: (1) Weigh 50.0g of the dehydrated filter cake sample obtained in step (4) of Example 2, place it in a beaker, add 200mL of anhydrous ethanol to soak and wash twice to terminate the existing hydration reaction and replace the free water, and then transfer it to a vacuum drying oven with the temperature set at 40℃ and dry it at a constant temperature for 24 hours to obtain the dried filter cake sample.

[0063] (2) Place the above-mentioned dried filter cake sample in an agate mortar and grind it by hand until it passes through a 325-mesh standard test sieve. Collect the powder that passes through the sieve as the sample to be tested.

[0064] (3) The X-ray diffractometer was used to scan and analyze the sample. The instrument was equipped with a Cu-Kα radiation source, the working tube voltage was set to 40kV, the tube current was set to 40mA, the scanning range 2θ was set to 5 degrees to 60 degrees, the scanning step size was 0.02 degrees, and the scanning speed was 2 degrees / minute.

[0065] (4) Import the original diffraction data obtained by scanning into the phase analysis software, remove the background and smooth it, extract the 2θ value of the main characteristic diffraction peak and the interplanar spacing d value, and compare and calibrate it with the powder diffraction standard card of the International Diffraction Data Center.

[0066] Based on the above tests, the main characteristic diffraction peak parameters and phase calibration results of the dehydrated filter cake in Example 2 are shown in Table 2.

[0067] Table 2. X-ray diffraction characteristic peaks and phase identification data of the dehydrated filter cake in Example 2 Note: In Table 2, "-" indicates that the phase has an amorphous or low crystallinity structure and there is no completely corresponding standard PDF card number in the International Data Center for Powder Diffraction Standard Card Library.

[0068] in conclusion: Based on the data in Table 2 and the appendix Figure 2 The phase composition of the final solid product of Example 2 was analyzed. (See Table 2 and Appendix). Figure 2 The diffraction data showed diffraction peaks around 2θ of 9.08°, 15.76°, and 22.84°. Comparison with the standard card revealed that these characteristic peaks correspond to calcium sulfoaluminate hydrate. This result indicates that calcium ions, aluminate ions dissolved from coal gangue, and sulfate ions from the water combine during the reaction to form the corresponding crystalline phase products.

[0069] Broadened diffraction peaks are observed near 2θ values ​​of 34.87° and 40.52°. Based on the elemental composition of the reaction system, these peak shapes are presumed to correspond to characteristics of low-crystallinity or amorphous magnesium silicate hydrate precursors. This phenomenon indicates that magnesium ions in the water combine with added silicate ions to form an amorphous magnesium silicate hydrate precursor. Furthermore, characteristic peaks of the quartz phase are observed at positions such as 2θ value of 26.62°, which belong to unreacted residual minerals in the coal gangue raw material.

[0070] The above test data reflects the composition of the solid products. Sulfate and magnesium ions in the water react during the treatment process, transforming into crystalline calcium sulfoaluminate hydrate and amorphous magnesium silicate hydrate precursors, respectively, which then transition from the liquid phase to the solid phase. The test results provide phase data support for the material transformation process of this method in treating saline bodies.

[0071] Test Example 3: This test example is used to test the solid-liquid separation parameters of each group of slurry systems. The composite precipitated slurry (before pressure filtration) obtained after the aging stage in step (3) of Examples 1 to 4, and Comparative Examples 2 and 3, is used as the test object. The experimental steps are as follows: (1) 500 mL of composite precipitate slurry samples with a temperature of 55°C to 65°C were extracted from the reaction vessels of Examples 1 to 4, Comparative Examples 2 and 3, respectively. The actual temperature of each sample was recorded at the time of extraction, and the samples were placed in a constant temperature water bath to maintain the original temperature for testing.

[0072] (2) Equip a Buchner funnel vacuum filtration device with an effective filtration area of ​​50 cm². 2 Lay out quantitative filter paper with a pore size of 0.45 μm, wet it with a small amount of deionized water and then vacuum dry it to make it adhere tightly to the base plate. Pour 100 mL of the slurry sample to be tested into the Buchner funnel at once, turn on the vacuum pump, and adjust the vacuum level to a constant 0.05 MPa.

[0073] (3) Starting from the first drop of filtrate, record the cumulative filtrate volume (V, unit: mL) collected at different time points (t, unit: s). The test continues until the filter cake surface loses its liquid luster and dry cracks appear. Combining the dynamic viscosity of the filtrate, the oven-dry mass of the filter cake, and the filtration area, calculate the filter cake specific resistance value of each group of slurries by plotting the relationship curve between filtration time (t / V) per unit filtrate volume and the cumulative filtrate volume (V) and obtaining the slope of the straight line.

[0074] (4) Collect the dewatered filter cake discharged from each group of actual filter press processes (i.e., after plate and frame filter press in step (4) of each embodiment and comparative example). Randomly sample and mix different parts of each group of filter cake, and weigh about 50.0g of wet material as wet weight. Place the wet material in an electric heating forced-air drying oven at 105℃ and dry it to constant weight, and weigh the oven-dry material. Calculate the moisture content of each group of filter cakes based on the difference between wet weight and oven-dry weight.

[0075] The solid-liquid separation performance data of each group of slurries after the above tests are shown in Table 3.

[0076] Table 3. Test data of filter cake specific resistance and filter cake moisture content for each slurry system in conclusion: Based on the data in Table 3 and the appendix Figure 3 The solid-liquid separation characteristics of each slurry group were analyzed. In the constant pressure filtration test, the slope of the t / V vs. V curve was positively correlated with the specific resistance of the filter cake. (See Table 3 and Appendix...) Figure 3 As shown in (a), the filter cake specific resistance of the slurries in Examples 1 to 4 ranges from 1.67 to 1.92 × 10⁻⁶. 12 The moisture content of the filter cake after plate and frame filtration was below 40% within the range of m / kg. The test results are within the parameter range of conventional industrial slurry dewatering operations.

[0077] Comparative Example 2: Water glass and calcium hydroxide were added simultaneously under strongly alkaline conditions. (See attached...) Figure 3As shown in (b), the slope of its t / V curve is increased compared to the example, and the corresponding filter cake specific resistance in Table 3 is 34.61 × 10⁻⁶. 12 The filter cake moisture content was 74.3% (m / kg). In a high pH environment, magnesium ions in the water formed magnesium hydroxide colloid. Magnesium hydroxide colloid has high water retention and compressibility, making it prone to clogging the filter cloth pores during filtration. This example uses pre-addition of water glass, where magnesium ions combine with silicate ions to form amorphous magnesium silicate hydrate precursors, reducing the probability of colloid clogging and maintaining the porosity of the slurry.

[0078] Comparative Example 3 did not contain sodium gluconate. Test results showed that its filter cake specific resistance was 8.12 × 10⁻⁶. 12 The dehydration performance was lower than in the example (m / kg). Without the addition of sodium gluconate, the system lacked appropriate coordination and retarding regulation. Calcium ions participated in the reaction more rapidly, increasing the crystal nucleation rate and generating more microcrystalline particles, leading to an increase in the proportion of fine powder in the slurry and thus increasing filtration resistance. The test data reflect the influence of reagent addition sequence and component type on slurry filtration performance.

[0079] Test Example 4: This test case is used to test the removal of core ions in water under different process conditions. The effluents obtained from the processes of Examples 1 to 4, and Comparative Examples 1, 3, and 4 are used as test objects. The experimental steps are as follows: (1) Collect the final effluent water samples of Examples 1 to 4, Comparative Examples 1, 3 and 4 before the reverse osmosis membrane pretreatment stage. Filter each water sample through a polyethersulfone microporous membrane with a pore size of 0.22 μm to remove residual suspended particles. Take the filtered filtrate and dilute it stepwise with deionized water according to a set ratio to ensure that the concentration of the analyte ion is within the linear range of the standard curve of the detection instrument.

[0080] (2) A series of standard solutions with concentration gradients of sulfate, magnesium, and calcium ions were prepared using mixed standard substances. The standard solutions were tested using an ion chromatograph to establish a standard curve of retention time versus peak area of ​​corresponding ion conductivity response.

[0081] (3) The diluted water samples were sequentially injected into the ion chromatograph for analysis. For anion analysis, a carbonate / bicarbonate system was used as the eluent, and for cation analysis, a methanesulfonic acid system was used as the eluent. The chromatographic data of each sample were recorded, and the peak area corresponding to the target ion was extracted.

[0082] (4) Calculate the diluted ion concentrations in each water sample based on the standard curve, and multiply by the corresponding dilution factor to obtain the actual residual concentrations of sulfate, magnesium, and calcium ions in the final effluent of each group. Combine this with the initial ion concentrations in the raw water to calculate the corresponding removal rates. The initial ion concentrations of the raw water used for calculation are set as follows: sulfate 8652.5 mg / L, magnesium ion 2146.8 mg / L, and calcium ion 1273.5 mg / L.

[0083] The residual concentration and removal rate of characteristic ions in each group of water samples after the above tests are shown in Table 4.

[0084] Table 4. Test data on residual concentration and removal rate of core ions in the final effluent of each group. in conclusion: Based on the data in Table 4 and the appendix Figure 4 The effects of different process conditions on the removal of sulfate and other ions in water were analyzed. Table 4 shows that the residual concentrations of sulfate, magnesium, and calcium ions in the effluent of Examples 1 to 4 were low, with removal rates exceeding 95%. Figure 4 (a) shows that the characteristic peak area of ​​sulfate ions is small near the retention time of 18 minutes in Example 2. The test data indicate that, under the process parameters of the example, the target ions in the water participated in the reaction and transferred to the solid phase.

[0085] observe Figure 4 (b) The three curves of Comparative Example 1, Comparative Example 3 and Comparative Example 4 basically overlap in the retention time period of 0 to 16 minutes and 20 to 25 minutes. The overlapping region mainly corresponds to the response of common background ions (such as chloride ions) and the baseline. The difference of the three curves is concentrated in the sulfate characteristic elution time period of 16 to 20 minutes.

[0086] Based on the data in Table 4, Comparative Example 1 used unactivated coal gangue powder, with a residual sulfate concentration of 6854.2 mg / L and a removal rate of 20.78%. Figure 4 (b) shows the largest sulfate peak area. Unactivated coal gangue is unlikely to release sufficient active aluminum under alkaline conditions, and the system lacks a precursor for the synthesis of calcium sulfoaluminate hydrate. Insufficient active aluminum source prevents sulfate ions from entering the mineral lattice, thus leaving them in the liquid phase.

[0087] Comparative Example 3, without the addition of sodium gluconate, had a residual sulfate concentration of 2865.4 mg / L. The lack of surface regulation and retarding effects from sodium gluconate in this system allowed calcium ions to combine and precipitate in the early stages of the reaction, coating the particle surface. This surface coating hindered further dissolution and mass transfer of internal components, reducing the sulfate mineralization and removal rate.

[0088] In Comparative Example 4, the aging stage temperature was set at 85℃, and the sulfate removal rate was 52.01%, indicating a higher sulfate concentration in the water compared to the previous example. Calcium sulfoaluminate hydrate has a specific thermodynamic stability range. Temperatures exceeding this range lead to mineral crystal structure degradation, causing the solidified sulfate to re-dissolve and re-enter the water. The test results reflect the impact of aging temperature on product stability and ion removal efficiency.

[0089] Test Example 5: This test case is used to test the compliance of the final effluent of each group as feed water for the reverse osmosis membrane system and the situation of secondary pollution. The effluent samples of Examples 1 to 4, and Comparative Example 5, which used dilute sulfuric acid as an acid adjuster in the final effluent pH adjustment step, are used as test objects. The experimental steps are as follows: (1) The turbidity of the water samples to be tested was measured using a turbidity meter. The final effluent water samples before reverse osmosis membrane pretreatment in each embodiment and Comparative Example 5 were injected into special sample bottles. After wiping the surface of the sample bottle clean and allowing it to stand to expel tiny air bubbles, the sample bottle was placed in the turbidity meter measuring tank to read and record the turbidity value of the water.

[0090] (2) The water filtration characteristics were tested using a standard sludge density index meter. A polyethersulfone microporous membrane with a pore size of 0.45 μm and a diameter of 47 mm was placed flat in the filter of the meter. The inlet valve was opened and the system pressure reducing valve was adjusted to keep the inlet gauge pressure constant at 0.207 MPa (30 psi) during the test.

[0091] (3) Open the filter outlet valve and collect the filtrate using a graduated cylinder. Simultaneously start a stopwatch to measure and record the time required to initially collect 500 mL of water sample, denoted as t0. Maintain continuous filtration under constant pressure. Repeat the above collection operation at the 5th, 10th, and 15th minutes of filtration, measuring and recording the time required to collect 500 mL of water sample, denoted as t5, t10, and t15 respectively. Combine this with the formula SDI... 15 =(1-t0 / t15)×100 / 15, calculate the silt density index (SDI) for each water sample.

[0092] (4) Take the filtrate after filtration of each group of water samples, and use ion chromatography to quantitatively detect sulfate ions in the water samples to evaluate the effect of the selected acid regulator on the terminal ion composition of the system.

[0093] Based on the above tests, the conventional influent parameters and sulfate concentration data of each group of water samples are shown in Table 5.

[0094] Table 5. Turbidity and SDI of water samples in each group 15 and sulfate concentration test data in conclusion: According to Table 5 and Appendix Figure 5 The data were analyzed to determine the water quality indicators for the treated effluent of each group, which were then used as the feed water for the subsequent reverse osmosis membrane system. Table 5 shows that the turbidity of the final effluent from Examples 1 to 4 ranged from 0.35 to 0.45 NTU. (Appendix) Figure 5 The curve reflects the change in filtration time during the measurement process. Combined with the SDI calculated in Table 5 for the example,... 15 The values ​​range from 2.18 to 2.81. The above turbidity is related to SDI. 15 The test results all met the requirements for feed water in a conventional reverse osmosis system (turbidity not greater than 1.0 NTU, SDI). 15 The test data indicates that, after the aforementioned solid-liquid separation and related treatment processes, suspended particles and colloidal components in the water body were effectively retained, meeting the physical water quality requirements for subsequent membrane desalination treatment.

[0095] Comparative Example 5 used dilute sulfuric acid as an acidifier in the effluent pH adjustment step. Table 5 shows that the turbidity and SDI of the effluent from Comparative Example 5 are related. 15 The numerical values ​​are similar to those in the example, but the sulfate concentration in the water reached 3584.2 mg / L, higher than that in the example group. In the subsequent reverse osmosis membrane desalination stage, as the permeate of freshwater and the volume of concentrate decrease, the ion concentration in the liquid phase will increase exponentially. The introduction of added sulfate increases the ion product of sulfate and residual calcium and magnesium ions on the concentrate side, increasing the possibility of slightly soluble sulfate crystallizing and precipitating on the membrane surface. This comparative test reflects that selecting non-sulfate acidic regulators such as carbon dioxide at the end of the saline system treatment helps maintain the permeate quality of the initial mineralization desulfurization process and control the inorganic scaling conditions of the subsequent membrane separation system.

[0096] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these specific embodiments are merely illustrative. Those skilled in the art can omit, substitute, and modify the details of the above methods in various ways without departing from the principles and essence of the present invention. For example, combining the above method steps to perform substantially the same function and achieve substantially the same result using substantially the same method falls within the scope of the present invention.

Claims

1. A method for co-treating brackish water from open-pit coal mines using coal gangue, characterized in that, Includes the following steps: Under stirring conditions, thermally activated coal gangue powder is added to the brackish water of the open-pit coal mine. After mixing evenly, liquid sodium silicate is added in a pulse manner, followed by sodium gluconate and continuous mixing to form a slurry, thus obtaining a primary slurry. Calcium hydroxide powder was added to the primary slurry to increase the pH value of the system, followed by heating and constant-temperature dissolution reaction to obtain an activated slurry. The heating rate is controlled to heat the activating slurry, the stirring speed is reduced, and the slurry is aged at a constant temperature under a low shear flow field to generate a composite precipitate slurry. The composite precipitate slurry is pumped to a filter press for dewatering, and the dewatered filter cake and high-temperature filtrate are collected after unloading. The high-temperature filtrate is cooled to obtain a cooled filtrate. Carbon dioxide gas is introduced to adjust the pH value of the cooled filtrate. An aqueous solution of polyacrylamide is added as a micro-flocculator. The solution is then introduced into an ultrafiltration membrane module for filtration and separation, where fine colloids are retained. The pretreated reverse osmosis effluent is collected.

2. The method for co-treating brackish water from open-pit coal mines using coal gangue according to claim 1, characterized in that, The method for preparing the thermally activated coal gangue powder includes the following steps: The raw coal gangue is crushed and mixed evenly to obtain crushed and homogenized material; The crushed and homogenized material is fed into a heating furnace and heated at a heating rate of 5°C / min. It is then kept at a constant temperature of 700°C to 800°C for 1.0 to 2.0 hours to undergo a dehydroxylation phase transition reaction, resulting in calcined clinker. The calcined clinker is cooled to 25°C, pulverized and sieved, and powder with a particle size not greater than 74 μm is collected to obtain the thermally activated coal gangue powder.

3. The method for co-treating brackish water from open-pit coal mines using coal gangue according to claim 1, characterized in that, The solid-liquid mass ratio of the thermally activated coal gangue powder to the brackish water from the open-pit coal mine is 1:6 to 1:

4. The molar ratio of silicon dioxide in the liquid sodium silicate to magnesium ions in the brackish water of the open-pit coal mine is 1.5:1 to 2.5:1; After the addition of the liquid sodium silicate, the pH value of the system is between 8.5 and 9.5; The amount of sodium gluconate added is 0.1% to 0.3% of the total mass of the thermally activated coal gangue powder; The stirring speed for the continuous mixing pulping is set to 120 rpm to 150 rpm, and the continuous mixing pulping time is 30 minutes to 45 minutes.

4. The method for co-treating brackish water from open-pit coal mines using coal gangue according to claim 1, characterized in that, During the process of adding calcium hydroxide dry powder to the primary slurry, the molar ratio of the total effective calcium provided by the dissolved calcium ions in the brackish water of the open-pit coal mine and the added calcium hydroxide dry powder to the sulfate ions in the brackish water of the open-pit coal mine is controlled to be 3.0:1 to 3.5:1, and the pH value of the system is raised to 11.5 to 12.

0. The heating temperature for the isothermal dissolution reaction is set to 40°C to 45°C, and the duration of the isothermal dissolution reaction is 1.5 hours to 2.0 hours.

5. The method for co-treating brackish water from open-pit coal mines using coal gangue according to claim 1, characterized in that, During the process of heating the activated slurry by controlling the heating rate, the heating rate is 1.5℃ / min to 2.5℃ / min, and the target heating temperature is 55℃ to 65℃. The stirring speed for constant temperature aging is set to 40 rpm to 60 rpm, and the aging time is 2.5 hours to 3.0 hours.

6. The method for co-treating brackish water from open-pit coal mines using coal gangue according to claim 1, characterized in that, The filter press is a diaphragm plate and frame filter press. The filter press dewatering process directly dewaters the composite precipitate slurry at a temperature of 55°C to 65°C, with the feed pressure controlled at 0.4MPa to 0.6MPa and the pressing pressure controlled at 1.0MPa to 1.2MPa.

7. The method for co-treating brackish water from open-pit coal mines using coal gangue according to claim 1, characterized in that, The high-temperature filtrate is cooled to obtain a cooled filtrate with a temperature of 40°C to 45°C. The volume purity of the carbon dioxide gas is 99.5%; The pH of the cooled filtrate after the reversion is 7.0 to 8.5; The mass fraction of the polyacrylamide aqueous solution is 0.1%, and the effective dosage is 3.0 mg / L.

8. The method for co-treating brackish water from open-pit coal mines using coal gangue according to claim 1, characterized in that, The continuous mixing and pulping, the isothermal dissolution reaction, and the isothermal aging are all carried out in an intermittent stirred reactor equipped with a variable frequency stirring device and a steam heating jacket.

9. The method for co-treating brackish water from open-pit coal mines using coal gangue according to claim 6, characterized in that, The filter press dewatering operation is as follows: The composite sediment slurry is pumped into the diaphragm plate and frame filter press, and after feeding is completed, the diaphragm press is started for dewatering.

10. The method for co-treating brackish water from open-pit coal mines using coal gangue according to claim 1, characterized in that, The carbon dioxide gas is introduced into the cooled filtrate using a microporous aeration disc.